2019
DOI: 10.3847/1538-4365/ab0ec5
|View full text |Cite
|
Sign up to set email alerts
|

A Possible ∼20 yr Periodicity in Long-term Optical Photometric and Spectral Variations of the Nearby Radio-quiet Active Galactic Nucleus Ark 120

Abstract: We study the long-term variability in the optical monitoring database of Ark 120, a nearby radio-quiet active galactic nucleus (AGN) at a distance of 143 Mpc (z = 0.03271). We compiled the historical archival photometric and spectroscopic data since 1974 and conducted a new two-year monitoring campaign in 2015-2017, resulting in a total temporal baseline over four decades. The long-term variations in the optical continuum exhibit a wave-like pattern and the Hβ integrated flux series varies with a similar behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 91 publications
2
33
0
Order By: Relevance
“…Possible interpretations of periodicities are discussed in many works [7,[9][10][11]30,31,35,36,50,51,54,70]. Assuming circular orbits in the disk as we did here, we suggest that possible source of periodicity should be in the AD, amplifying an emission contribution at that radius.…”
Section: Possible Interpretationssupporting
confidence: 61%
See 3 more Smart Citations
“…Possible interpretations of periodicities are discussed in many works [7,[9][10][11]30,31,35,36,50,51,54,70]. Assuming circular orbits in the disk as we did here, we suggest that possible source of periodicity should be in the AD, amplifying an emission contribution at that radius.…”
Section: Possible Interpretationssupporting
confidence: 61%
“…Unfortunately, it is hard to find cases of AGN light curves with several repeating patterns [4,5,9,10,29,30,36], needed for the clear detection of periodicity, above the red noise level, since the length of current AGN monitoring campaigns are of the order of orbiting time scales. Therefore, as an indicator of orbiting effects we could be tracing the broad emission line shifts, and if the periodicity in radial velocity curves is the same, it could indicate that the mechanism which drives both curves could be linked to the orbiting within the broad line region [7,[9][10][11]31,37]. Radial velocity curves are harder to obtain due to even shorter records of spectral observations, and therefore only a few candidates are detected, such as NGC 4151 with a 15.9 year periodicity [6,7], NGC 5548 with a ≈15 year periodicity [9,10], and Ark 120 with a ≈20 year periodicity [11].…”
Section: Supermassive Black Hole Binariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The optical flux periodicity may be caused by accretion rate changes due to the intrinsic binary orbital tidal torque modulation (e.g., MacFadyen & Milosavljević 2008;Shi et al 2012;Roedig et al 2012;D'Orazio et al 2013;Farris et al 2014;Tang et al 2018), and/or the apparent Doppler boost modulation from the highly relativistic motion of gas in the mini accretion disk around the secondary BH (e.g., D'Orazio et al 2015b;Charisi et al 2018). While 100 quasars with candidate periodicity have been proposed as evidence for BS-BHs (e.g., Valtonen et al 2008;Graham et al 2015a,b;Liu et al 2015Liu et al , 2016Bon et al 2016;Charisi et al 2016;Zheng et al 2016;Li et al 2019), even the strongest candidate periodicity has been shown to be subject to false positives due to stochastic quasar variability given the uneven sampling, limited time baseline, and/or relatively low sensitivity. For example, the blazar OJ 287 has been suggested to host a BSBH based on the evidence for a 12-year periodicity in the optical and radio light curves (e.g., Sillanpaa et al 1996;Valtaoja et al 2000;Valtonen et al 2016), where the double-peaked flares have been interpreted as the result of a secondary BH punching through the accretion disk of the primary (e.g., Takalo 1994;Valtonen et al 2008) or accretion disk precession driven by the gravitational torque of a companion BH (e.g., Katz 1997).…”
Section: Introductionmentioning
confidence: 99%